(untitled) (Ilm fan taraqqiyotida raqamli iqtisodiyot va zamonaviy ta’limning o’rni hamda rivojlanish omillari, 2025)
Abstract: Tax aversion and the growth of the shadow economy pose significant challenges to governments worldwide. This conference paper explores the potential of reducing tax aversion by optimizing the structure of the tax burden. Through an analysis of international experiences and a review of relevant literature, this paper examines the economic, social, and institutional factors influencing tax aversion and informal economic activities. The findings highlight the importance of context-specific interventions in curbing tax aversion and promoting formal economic engagement.